Ancestry versus Ethnicity: The Complexity and Selectivity of Mexican Identification in the United States - Brian Duncan; Stephen Trejo (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Using microdata from the 2000 U.S. Census, we analyze the responses of Mexican Americans to questions that independently elicit their "ethnicity" (or Hispanic origin) and their "ancestry". We investigate whether different patterns of responses to these questions reflect varying degrees of ethnic attachment. For example, those identified as "Mexican" in both the Hispanic origin and the ancestry questions might have stronger ethnic ties than those identified as Mexican only in the ancestry question. How U.S.-born Mexicans report their ethnicity/ancestry is strongly associated with measures of human capital and labor market performance. In particular, educational attainment, English proficiency, and earnings are especially high for men and women who claim a Mexican ancestry but report their ethnicity as "not Hispanic". Further, intermarriage and the Mexican identification of children are also strongly related to how U.S.-born Mexican adults report their ethnicity/ancestry, revealing a possible link between the intergenerational transmission of Mexican identification and economic status.
Keywords: 330